Watching More Than The Discovery Channel : Export Cycles And Diversification In Development - Brenton, Paul, 1961- 1961- (The World Bank, 2007)
This paper examines the export performance of 99 countries over 1995-2004 to understand the relative roles of export growth through "discovery" of new products and growth during post-discovery phases of the export product cycle -- acceleration and maturation -- in existing markets and expansion into new geographic markets. The authors find that expanding existing products in existing markets (growth at the intensive margin) has greater weight in export growth than diversification into new products and new geographic markets (growth at the extensive margin). Moreover, growth into new geographic markets appears to be more important than discovery of new export products in explaining export growth. Of particular importance is whether an exporting country succeeds in reaching more national markets that are already importing the product it makes. This geographic index of market penetration is a powerful explanatory variable of export performance. This suggests that governments should not focus solely or even primarily on the discovery channel, but also seek to identify and address market failures that are constraining exporters in subsequent phases of the export cycle